Dificultăţi de acces la serviciile publice de sănătate în România - Doboș, Cristina (Calitatea Vieții, 2006)
The acces to health and education services is legally considered as an individual fundamental right in all European countries. In spite of all these constitutional rights, reality shows that all systems of health and education have difficulties in covering the people with services. These problems are minor in West European countries but they are accentuated in some former comunist countries which are still dealing with lack of infrastructure of services providers, low life standard of population and low finance of health services. This article deals with the problems of acces of the population to public health services in Romania, after 1989. I am interested in the factors that limit this acces and the social groups which are in risk. I use secondary data analysis, includind the comment of the data from Eurobarometer (2002), in order to see how Romania stands, comparing with other European countries (EU members or candidates).